Impact of Different Curing Techniques in Evaluating the Strength of the Roller Compacted Concrete Containing Waste Materials (Journal of Engineering, 2025)
The main objective of this laboratory study was to produce environmentally friendly, sustainable roller-compacted concrete (SRCC) that meets the required strength by utilizing waste building materials such as waste thermostone block as a partial volume replacement of fine aggregate by two percentages (15% and 30%) and filler by 50%. Along with standard curing, three different curing regimes were tested: spray-water, liquid-membrane compound (Sika Antisol-WB), and damp-burlap. Regarding the curing methods, the liquid-membrane compound achieved the best results compared to standard-curing, followed by damp-burlap. On the other hand, spray-water resulted in the poorest performance, yielding lower results than standard-curing. The results showed that the SRCC mixture containing waste thermostone block (by 15% substitute of fine aggregate and by 50% substitute of filler) improved the compressive, flexural, and tensile strengths by 1.66%, 1.51%, and 1.68%, respectively, after 28 days of standard-curing compared to the reference-mixture. While the SRCC mixture containing waste thermostone block (by 30% substitute of fine aggregate and by 50% substitute of filler) deteriorated the compressive, flexural, and tensile strengths by 4.97, 4.24, and 3.98%, respectively, after 28 days of standard-curing compared to the reference-mixture.